Enzymatic incorporation and fluorescent labelling of cyclooctyne-modified deoxyuridine triphosphates in DNA. - Ren, X; Gerowska, M; El-Sagheer, A; Brown, T (Elsevier, 2014)
The amino group of 5-aminopropargyl-2'-deoxyuridine-5'-triphosphate was labelled with dibenzocyclooctyne (DIBO) and two derivatives of bicyclo [6.1.0] non-4-yne (BCN) with short and long linkers to produce three different cycloalkyne-modified deoxyuridine triphosphates. BCN was successfully incorporated into DNA at multiple sites by enzyme-mediated primer extension and the polymerase chain reaction (PCR). Efficient fluorescent labelling of the BCN-DNA and DIBO-DNA with Cy3-azide was demonstrated.